Upaya Membangun Kesadaran Keamanan Siber pada Konsumen E-commerce di Indonesia - Nur Rohmah, Ratri (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2022)
Technological developments change people's behavior in buying and selling transactions. Consumer's shopping habits switched to e-commerce. However, transactions in e-commerce not only have a positive impact but also have a negative impact. consumers suffer losses due to cybercrime. Consumers need security. Cyber security is not only a device, but also human needs to provide an understanding of cyber security awareness. This study aims to determine the cybersecurity awareness program that can be built to protect e-commerce players. The method used is descriptive analysis conducting a literature study based on references. The results of the study indicate that efforts to build cybersecurity awareness among e-commerce players can be carried out through awareness programs or cybersecurity awareness programs. This awareness program is very simple and not too formal. It is necessary to prepare several aspects such as structure, priorities, materials, presentation and budgeting. The selected material can be searched directly for users, namely e-commerce actors. On the other hand, support from market providers is also needed to campaign for this cyber security awareness program. It is also necessary to carry out continuous evaluation of this cybersecurity awareness building effort to get feedback for improvement.